SHALAWAT MASYISYIYAH DAN PENINGKATAN SPRITUALITAS: STUDI ANALISIS PANDANGAN SANTRI PONDOK DARUT TAUHID PESANTREN ZAINUL HASAN - Najwa Najiyah Ubudiyah; Syafi'i, Imam; Islam , Saiful (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
This article discusses Sholawat Masyisyyah written by Sayyid Abdussalam bin Masyisy, born in 599 H/1198 AD, which became a routine activity for the students of Pondok Darut Tauhid. This research uses a qualitative method with a field approach (field research), researchers use qualitative methods to research in natural settings and this research does not make treatments, because researchers in collecting data are emic, that is, based on the views of the data source, not the researchers' views. Where data was collected directly at the research location, namely Pondok Darut Tauhid Islamic Boarding School Zainul Hasan Genggong. The results of the research show that the spirituality of practicing Shalawat Masyisyiyah for students is not only limited to peace of mind, but also contributes to making various matters of life easier. Apart from that, Shalawat Masyisyiyah is believed to be able to be a means of facing various challenges and resistance from enemies. Keywords: pondok darut tauhid, shalawat masyisyiyah, spsirituality